Box 1. ‘The Emperor's New Clothes’‘The Emperor's new clothes?’ Healthcare professionals’ perceptions of the nursing associate role in two UK National Health Service hospitals: A qualitative interview study - Carolyn Spring; Enrique Castro-Sánchez; Mary Wells (International Journal of Nursing Studies Advances, 2024)
Background: The introduction of nursing associates in England in 2017 as a professional ‘bridging’ role aimed to mitigate chronic staffing shortages, enable career progression of healthcare assistants and release registered nurses to provide more complex care. Limited evidence exists about the alignment between the identity and purpose of nursing associate roles described by the UK independent regulator, the Nursing & Midwifery Council, and the expectations, obligations, and team dynamics encountered in practice. Purpose: Investigate the perceptions of nursing associate roles through the views and experiences of role holders, registered nurses, and healthcare assistants. Setting: Two British National Health Service (NHS) Hospital Trusts in London, England (UK). Methods: For this registered service evaluation, data were collected via in-person, semi-structured interviews. Verbatim transcripts were coded inductively. An adapted framework analysis method, suitable for use with Excel, was applied to support the identification of cross cutting themes. We used the Standards for Reporting Qualitative Research checklist for reporting this study. Results: Eleven registered nurses, five nursing associates, and five healthcare assistants participated. Their experiences seldom reflected the policy vision of the nursing associate role in practice. Several participants likened the nursing associate role to the fable of the ‘Emperor's New Clothes’ in which expectations and reality diverge. With this over-arching theme, four sub-themes were identified: (1) preparedness of organisational infrastructure to support this role; (2) credibility of the role in practice; (3) perceived organisational “blindness” to the ambiguities of the role and (4) increasing task orientation and segmentation in care delivery. Conclusion: There is a discrepancy between the identity of the nursing associate role as imagined in the policy agenda and its reality in practice. There is a need for more protected and well-defined training, clear role boundaries, and accessible career progression pathways for nursing associates. Moreover, honest dialogue at an organisational and policy level must continue, so that the challenges and opportunities of the nursing associate role are properly realised. Tweetable abstract: Emperor's new clothes! Experiences and views of new nursing associate roles in NHS (UK) acute hospitals @CarolynSpring3.